Cost Effectiveness of Immediate Tracheostomy versus Early Tracheostomy in Decompressive Craniectomy Patients: A Retrospective Study - Hasan, Hezry Abu (2021)
Cost Effectiveness of Immediate Tracheostomy versus Early Tracheostomy in Decompressive Craniectomy Patients: A Retrospective Study Dr. Hezry bin Abu Hasan ’, Dr. Sofan bin Zenian ’, Dr. Regunath Kandasamy 2, Prof. Dato’ Dr. Syed Mohamed Aljunid Syed Junid 3'4. 1. Neurosurgical Unit, Hospital Queen Elizabeth, Kota Kinabalu, Sabah, Malaysia. 2. Department of Neurosurgery, Hospital Universiti Sains Malaysia (HUSM), Kubang Kerian, Kelantan, Malaysia. 3. Health Policy and Management Department, Faculty of Public Heal±, Kuwait University, Kuwait City, Kuwait. 4. International Center for Casemix and Clinical Coding (ITCC), National University of Malaysia, Kuala Lumpur, Malaysia. Traumatic Brain Injury (TBI) patients often present with refractory intracranial hypertension, necessitating a supratentorial decompressive craniectomy to relieve malignant intracranial pressure and prevent further neurological insult. However, due to the poor neurological condition of these patients, many are electively intubated and put on mechanical ventilation to protect tire airway and facilitate cerebral protective measures. Unfortunately, as a x result of poor and prolonged neurological recovery, many patients have to be put on tracheostomy in view of prolonged intubation. Prolonged mechanical ventilation also inefficiently utilizes the already limited mechanical ventilators and Intensive Care Unit (ICU) beds. In an attempt to maximize our limited hospital resources, we innovate a new method of tracheostomy timing strategy by performing the tracheostomy in the same setting as the supratentorial decompressive craniectomy (Immediate Tracheostomy) in patients who are anticipated to require prolonged mechanical ventilation. We attempt to answer ‘How early should Early Tracheostomy be done?’ by comparing the clinical and cost-saving benefit of the Immediate Tracheostomy strategy. A retrospective study on patients requiring a supratentorial decompressive craniectomy and tracheostomy done within 7 days of the cranial surgery from January 2013 to December 2019 in Hospital Queen Elizabeth was done. Patients receiving a tracheostomy in the same setting of their supratentorial decompressive craniectomy were assigned to the Immediate Tracheostomy (IT) group, whereas those who received a tracheostomy within 7 days of their cranial surgery was assigned to the Early Tracheostomy (ET) group. Normally distributed quantitative data was analyzed using the independent T-test, while non-normally distributed data was analyzed using the Mann-Whitney U-test. Qualitative variables were analyzed with a Chi-square test. Cost of treatment of each patient was obtained based on Malaysian costing database provided by Casemix System MY-DRG. Of 411 patients reviewed, a total of 63 patients were included in the study. 21 patients (33.3%) were allocated to the Immediate Tracheostomy (IT) group and 42 patients (66.7%) in the other. Patients in the Immediate Tracheostomy (IT) group had significantly lower total GCS scores (Median (IQR): 6 (3) versus 9 (4), p = 0.011), reduced duration of mechanical ventilation (Median (IQR): 72 hours (48) versus 120 hours (72), p = 0.001) and sedation (Median (IQR): 48 hours (24) versus 72 hours (54),/? = 0.001), and shorter ICU length of stay (Median (IQR): 72 hours (48) versus 144 hours (96), p = 0.001). Cost reduction with the Immediate Tracheostomy (IT) strategy was estimated to be RM 18,463.14 — RM 39,223 per patient. The diagnosis of severe TBI, total GCS score <6 on presentation, and the presence of Intraventricular Hemorrhage (IVH) on CT brain imaging were identified as possible indicators for patients who will benefit from the Immediate Tracheostomy (IT) strategy. The Immediate Tracheostomy strategy has shown evidence of increasing ICU bed turnover and reducing the cost of treatment. Patients presenting with a total GCS of < 6 and presence of IVH on CT Brain were seen to benefit from Immediate Tracheostomy. With the clinical and treatment cost benefits seen, the Immediate Tracheostomy (IT) strategy should be considered a viable option for the management of Traumatic Brain Injury patients undergoing supratentorial decompressive craniectomy.